2014
DOI: 10.1016/j.micres.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a glyphosate-degrading rhizosphere strain, Enterobacter cloacae K7

Abstract: Plant-growth-promoting rhizobacteria exert beneficial effects on plants through their capacity for nitrogen fixation, phytohormone production, phosphate solubilization, and improvement of the water and mineral status of plants. We suggested that these bacteria may also have the potential to express degradative activity toward glyphosate, a commonly used organophosphorus herbicide. In this study, 10 strains resistant to a 10 mM concentration of glyphosate were isolated from the rhizoplane of various plants. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 28 publications
2
54
0
9
Order By: Relevance
“…None of the pesticides could support molybdenum reduction, however, the bacterium could grow on glyphosate (Figure 2d). Numerous glyphosatedegrading bacteria has been isolated and include Enterobacter cloacae (Kryuchkova et al, 2014), Ochrobactrum spp. (Hadi et al, 2013), Pseudomonas fluorescens (Zboinska et al, 1992), Agrobacterium radiobacter (McAuliffe et al, 1990), Pseudomonas sp.…”
Section: Pesticides As Electron Donors For Molybdenum Reduction and Imentioning
confidence: 99%
See 1 more Smart Citation
“…None of the pesticides could support molybdenum reduction, however, the bacterium could grow on glyphosate (Figure 2d). Numerous glyphosatedegrading bacteria has been isolated and include Enterobacter cloacae (Kryuchkova et al, 2014), Ochrobactrum spp. (Hadi et al, 2013), Pseudomonas fluorescens (Zboinska et al, 1992), Agrobacterium radiobacter (McAuliffe et al, 1990), Pseudomonas sp.…”
Section: Pesticides As Electron Donors For Molybdenum Reduction and Imentioning
confidence: 99%
“…Removal of glyphosate from soils is best carried out by bioremediation often employing glyphosate-degrading bacteria as the low con-centration of glyphosate in polluted soils make other form of remediation such as chemical and physical more expensive and unpractical. Examples of glyphosate-degrading bacterium reported include Enterobacter cloacae (Kryuchkova et al, 2014), Ochrobactrum spp. (Hadi et al, 2013), Pseudomonas fluorescens (Zboinska et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, numerous studies have shown microorganisms can degrade that glyphosate. Several potential glyphosate degrading microorganisms have been isolated from organophosphates contaminated soils such as Enterobacter cloacae (Kryuchkova et al, 2014), Geobacillus caldoxylosilyticus (Obojska et al, 2002), Pseudomonas spp. (Dick and Quinn, 1995), Rhizobium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are perhaps the most versatile and diversified organisms with regard to their nutritional requirements (Leckie, 2005). The development of an affordable and environmentally friendly bioremediation method using glyphosate-degrading bacteria is a promising approach for cleansing and restoring soils contaminated with this herbicide (Kryuchkova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although plant growth promotion rhizobacteria are commonly used to promote plant growth and control plant diseases, their potential use in bioremediation has also been explored (Narasimhan et al, 2003;Huang et al, 2005). Several studies have been conducted to isolate pure bacterial strains with degrading capability for potential uses such as the removal of glyphosate from soil and bioremediation of glyphosate-contaminated soils (Ermakova et al, 2008;Ahire et al, 2012;Kryuchkova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%